Considerations of neuroscience on freedom and responsibility - Ibáñez Blancas, Franklin (2017)
This article analyzes two well-known experiments in neuroscience (Joshua Green and Benjamin Libet), which question our common beliefs about freedom and responsibility. If we were not free or responsible, would be relevant our moral norms and laws? This texts is a defense of freedom and responsibility against hasty conclusions which might be inferred from those experiments.